Development of a Bispecific Antibody Targeting CD30 and CD137 on Hodgkin and Reed-Sternberg Cells - Rajendran, Sakthi; Li, Yating; Ngoh, Evelyn; Wong, Hiu Yi; Cheng, Man Si; Wang, Cheng-I; Schwarz, Herbert (Frontiers in Oncology, 2019)
Hodgkin Lymphoma (HL) is a malignancy that frequently affects young adults. Although, there are effective treatments not every patient responds, necessitating the development of novel therapeutic approaches, especially for relapsed and refractory cases. The two TNF receptor family members CD30 and CD137 are expressed on Hodgkin and Reed Sternberg (HRS) cells, the malignant cells in HL. We found that this co-expression is specific for HRS cells. Based on this discovery we developed a bispecific antibody that binds preferentially to the CD30, CD137-double positive HRS cells. The CD30, CD137 bispecific antibody gets internalized into HRS cells opening up the possibility to use it as a carrier for a toxin. This antibody also induces antibody-dependent, cell-mediated cytotoxicity in CD30, CD137-double positive HRS cells. The enhances specificity of the CD30, CD137 bispecific antibody to HRS cells makes it a promising candidate for development as a novel HL treatment.